Investigation of damage caused by partial shading of CuInxGa(1‐x)Se2 photovoltaic modules with bypass diodes. (3rd April 2016) - Lee, Ji Eun; Bae, Soohyun; Oh, Wonwook; Park, Hyomin; Kim, Soo Min; Lee, Dongho; Nam, Junggyu; Mo, Chan Bin; Kim, Dongseop; Yang, JungYup; Kang, Yoonmook; Lee, Hae‐seok; et al.
Abstract: This study evaluated the impact of partial shading on CuInxGa(1‐x) Se2 (CIGS) photovoltaic (PV) modules equipped with bypass diodes. When the CIGS PV modules were partially shaded, they were subjected to partial reverse bias, leading to the formation of hotspots and a possible occurrence of junction damage. In a module with a cadmium sulfide buffer layer, hotspots and wormlike defects were formed. The hotspots were formed as soon as the modules were shaded; the hotspots caused permanent damage (wormlike defects) in the CIGS module. Specifically, the wormlike defects were caused by the window layer, leading to increased recombination and decay of the solar cell properties. However, a CIGS module with a zinc sulfide buffer layer did not exhibit the formation of hotspots or any visual damage. The reverse bias breakdown voltage of the CIGS PV module with the cadmium sulfide buffer layer was higher than that of the CIGS PV module with the zinc sulfide buffer layer. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Electrical properties of CIGS photovoltaic module with bypass diode reduced after shading the module. In addition, damage occurred to the CIGS thin‐film module because of the shade effect in spite of operating bypass diode. It is because the module with the CdS buffer layer exhibited a shunt current lower than that of the module with the ZnS buffer layer during reverse bias, which occurred thermal breakdown in CIGS photovoltaic module with the CdS buffer layer under the shade condition.